Justice Collaborator In Disclosure Action Criminal Corruption - Fahmi Fauzi Amiruddin; Nur Fadhilah Mappaselleng; Syamsul Alam (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze the strength of the evidence of justice collaborators in disclosing corruption, and to determine the role of Justice Collaborators in disclosing Corruption. This study uses a normative research method using a library approach as the main source, such as library research. Descriptive data analysis techniques. The results of this study indicate the strength of evidence by Justice Collaborators as witnesses in corruption in disclosing corruption cases requires witnesses and evidence, effective case resolution indicates the seriousness of law enforcement officers in working together to uncover corruption. The important role of justice collaborators in uncovering corruption crimes is to provide crucial information and assist law enforcement officers in identifying perpetrators, as well as facilitating investigators and public prosecutors in finding facts in criminal cases in helping to uncover and ease the evidence process. The recommendation in this study is to provide awards or incentives for justice collaborators in providing significant information in uncovering corruption cases. Meanwhile, the regulation of justice collaborators is not clearly regulated in the regulations so that in making ideas regarding the regulation of protection for justice collaborators regarding prevention or disclosure of corruption crimes in the future, as well as related to how to impose sentences, clarity of requirements in the form of procedures and security for a justice collaborator.